Adaptive Reuse of ministerial buildings in Egypt to achieve sustainable urban development - Eman Ahmed; Rania Sorial; Farag Zaki (JES: Journal of Engineering Sciences)
Adaptive reuse is a sustainable strategy that repurposes existing buildings to minimize environmental impact, preserve cultural heritage, and support urban regeneration. This study evaluates the adaptive reuse potential of key ministerial buildings in Cairo following the relocation of government offices to the New Administrative Capital. A multi-criteria decision-making (MCDM) approach integrated with Geographic Information Systems (GIS) was employed to assess the suitability of reuse strategies based on five dimensions: architectural integrity, economic feasibility, environmental sustainability, legislative considerations, and social impact. The methodology involved spatial analysis, and site visits, utilizing overlay analysis and heat mapping to identify optimal reuse opportunities. Findings reveal that these buildings can be repurposed into innovation hubs, cultural centers, research facilities, hotels, and mixed-use developments, contributing to Cairo’s sustainable urban development. The Ministry of Education building is well-suited for scientific and medical research centers, the General Organization for Physical Planning building for urban heritage and planning initiatives, and the Ministry of Housing building for commercial, entrepreneurial, and hospitality functions due to its high economic viability. By leveraging data-driven spatial analysis and sustainability assessments, adaptive reuse can transform underutilized government assets into economically viable, environmentally sustainable, and culturally significant spaces, supporting Egypt’s urban development agenda.